Struggles and Experiences of Parents with Special Educational Needs Learners - Cercado, Delia; Pinili, Lilibeth; Cebe, Danilo; Cañete, Janine Joy; Añero, Marjorie (International Journal of Educational Studies, 2025)
This qualitative-phenomenological study explored the struggles and experiences of parents in managing the educational and developmental needs of children with special educational needs (SEN) at Dampas Elementary School, Tagbilaran City, Bohol. Using a validated five-part interview guide, in-depth interviews were conducted with ten purposively selected parents of SEN learners enrolled during the 2024–2025 school year. The research aimed to uncover the parenting strategies, challenges, and support needs of these families. Data were analyzed using thematic analysis, which revealed key themes related to parental practices: Guiding Healthy Habits and Language Development, Protecting Vulnerability Through Education, and Navigating Distraction and Learning Challenges. Challenges were categorized under emotional stress, lack of time and resources, and difficulty in understanding special education needs. Despite these struggles, many parents demonstrated resilience, commitment, and adaptive strategies to support their children. The study emphasizes the importance of strong school-home collaboration and tailored interventions to improve outcomes for SEN learners. Findings were used to propose an enhanced Parental Support and Practices Plan, with recommendations for educational stakeholders to strengthen systems that empower and support parents of SEN children.